Desempeño laboral de los trabajadores del Centro de Salud Puebloviejo - Garcia Valero, Leidy Suley (2019)
The present case study is the Labor Performance of the Workers of the Puebloviejo Health Center, it aims to propose solutions that allow to improve in a short term the situation of the labor performance of the health center, this case study consists of the following parts, First The problem where we find the case study topic and the causes that originated it, the justification is also argued and the objectives are stated explaining the purpose of the study. Second extracts all the investigation as it refers to the research background, foundations that support the case study. Third point out the methods and techniques used, data processing, analysis and interpretation of the survey, conclusions and recommendations